KEWENANGAN PENGAWAS TERMINAL DALAM MENGATASI TERMINAL BAYANGAN GADANG BUMIAYU - Wahyudi, Wahyudi; Marwiyah, Siti; Aribawa, M.Yustino (Gapenas Publisher, 2025)
This research is motivated by the widespread existence of shadow terminals that disrupt the order of public transportation, one of which is the Gadang Bumiayu Shadow Terminal in Malang City. The research problems focus on how the authority of terminal supervisors in handling shadow terminals and the supporting factors for the effectiveness of supervision. This study employs a socio-legal approach with empirical methods through interviews with terminal supervisors and literature review related to transportation regulations. The findings indicate that terminal supervisors hold the main authority to regulate, supervise, and control public transportation activities, including vehicle roadworthiness inspections, route enforcement, passenger boarding and alighting supervision, and initial law enforcement. However, this authority has not been fully effective due to limited personnel, lack of supporting facilities, weak inter-agency coordination, and low driver compliance. The effectiveness of supervision can be improved through terminal revitalization, regulatory harmonization between central and local governments, the use of digital technology, and multi-stakeholder collaboration. Thus, addressing shadow terminals requires not only law enforcement but also strengthening public transport governance that is responsive and service-oriented